Baicalein Enhances the Oral Bioavailability and Hepatoprotective Effects of Silybin Through the Inhibition of Efflux Transporters BCRP and MRP2 - Xu, Peng; Zhou, Hua; Li, Ya-Zhuo; Yuan, Zhong-Wen; Liu, Chang-Xiao; Liu, Liang; Xie, Ying (Frontiers in Pharmacology, 2018)
Although hepatoprotective properties of silybin are well documented, the clinic therapeutic efficacy is limited by its low bioavailability due to absorption rates, extensive phase II metabolism and biliary excretion. As our previous study indicated that metabolism enzyme may have limited effects on the PK behavior of silymarin, here we were aimed to increase the oral bioavailability and bio-efficacy of silybin through inhibiting active efflux. In Caco-2 and transfected MDCKII cell models, flavone baicalein significantly inhibited the efflux of silybin as a BCRP and MRP2 inhibitor. In addition, baicalein reduced the biliary excretion index (BEI) and biliary clearance of silybin conjugates in the sandwich-cultured rat hepatocyte (SCH) model, indicating the inhibition of baicalein in biliary excretion of conjugated silybin metabolites. Pharmacokinetic study demonstrated that baicalein significantly increased AUC and Cmax of silybin, suggesting the enhanced absorption in vivo. Moreover, co-administration silybin with baicalein boosted the liver protection, antioxidant, and anti-inflammatory effects of silybin in carbon tetrachloride (CCl4) induced liver injury model by comparing with silybin given alone. In sum, efflux transporters play a critical role for low bioavailability of silybin, while inhibition of BCRP and MRP2 by baicalein could significantly increase the absorption and bio-efficacy of silybin, which provide a new combination therapeutic approach for treating chronic liver diseases.